PENERAPAN METODE PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN KEMAMPUAN BERMAIN DRAMA PADA SISWA KELAS XII SMA 4 MATARAM TAHUN PELAJARAN 2019/2020 - Ramlah H. A. Gani; Nurdin Nurdin; Nunung Supratmi; Herman Wijaya (KOLONI, 2022)
This research aims to improve the ability to play drama by using problem-based motode in students of class XII High School 4 Mataram Year of Study 2019/2020. This research is carried out in the form of Classroom Action Research (PTK) or (Classroom Action Research), so that in learning using stages in the form of cycles. To obtain data on the results of the given actions, the teacher uses a test. While to see the increase in student learning activities that occur, observation methods are used. To analyze the data that has been obtained, quantitative descriptive techniques are used. The results of the study showed that student learning outcomes can increase in two cycles. This is evidenced by the fact that the increase in active participation of students in asking questions, responding to teacher questions and being able to work independently. It can also be proven by an increase in student learning outcomes. This is seen in the results of student learning performance tests that increased in cycle I the classical completion rate in cycle I (61.29%) while the classical completion rate in cycle II (80.65%). Based on the data obtained shows that learning using problem-based methods can improve the ability to play drama in students of class XII C High School 4 Mataram Year of Study 2019/2020. Keywords: Play Drama, method, problem-based, drama-based